Cultural Consumption of Film Camera - Jirasatthumb, Norachit; Khakhanmalee, Piyathida (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ วัตถุประสงค์ของบทความคือการศึกษารูปแบบวัฒนธรรมการบริโภคกล้องฟิล์ม โดยนำแนวคิดเศรษฐศาสตร์การเมืองของปิแอร์ บูร์ดิเยอ มาวิเคราะห์ประเด็นของ ทุน รสนิยม ฮาบิทัส และ แวดวง การวิเคราะห์ด้านทุนได้แบ่งกลุ่มตัวอย่างได้เป็น 4 ลักษณะตามระดับทุนทางเศรษฐกิจและวัฒนธรรม การวิเคราะห์ด้านรสนิยมบ่งชี้ว่าการบริโภคกล้องฟิล์มในปัจจุบันสอดคล้องกับรสนิยมแห่งความหรูหรา ซึ่งถูกขับดันด้วยฮาบิทัสที่ชื่นชอบความคลาสสิค ความต้องการท้าทายสิ่งใหม่ๆ และปลดปล่อยความสร้างสรรค์ การวิเคราะห์ยังชี้ให้เห็นว่าฮาบิทัสได้ถูกบ่มเพาะด้วยอิทธิพลจากปัจจัย ครอบครัว เพื่อน โซเชียลมีเดีย และรูปแบบการใช้ชีวิต การวิเคราะห์แวดวงชี้ให้เห็นข้อค้นพบที่สำคัญว่า กิจกรรมของผู้ชอบกล้องฟิล์มนั้นเป็นพื้นที่แห่งการช่วงชิงทุนระหว่างผู้คนในแวดวง ในขณะเดียวกันก็เป็นพื้นที่ๆ เปิดโอกาสให้เกิดการเลื่อนระดับของทุนได้ การศึกษาครั้งต่อไปควรติดตามกลุ่มตัวอย่างที่มีอยู่แล้ว เพื่อวิเคราะห์พลวัตของการเปลี่ยนแปลงระดับทุนที่อาจส่งผลต่อความคงทนของฮาบิทัสและแวดวงได้ ABSTRACT The objective of this article is to study the cultural pattern of film camera consumption by employing the political economy framework of Pierre Bourdieu in order to analyse the issues of capital, taste, habitus, and field. The analysis of capital classifies samples into four characteristics according to the degree of economic and cultural capital. The analysis of taste identifies that at the present, film camera consumption is consistent with the taste of luxury driven by habitus the joy of collecting, the need for new challenges and liberating creativity. The analysis also shows that habitus is cultivated by various factors such as, family, friend, social media, and life style. The analysis of field indicates an important finding that the activities of film camera lover clubs represent a space of competition for capital mobility among its members. Further study should follow up on these existing samples in order to analysis the dynamics of capital change that could affect the persistence of habitus and field.